COVID-19 and distortions in urban food market in India - Pallavi Rajkhowa; Lukas Kornher (Indian Economic Review, 2022)
In this paper, we study the effects of the spread of COVID-19 on retail and wholesale prices of urban markets in India, as well as price distortion between markets and the mark-up between retail and wholesale prices. Using fixed-effects panel regression models, we find that with the spread of COVID-19, prices increased for commodities with longer shelf-life such as pulses and processed items, while prices of vegetables such as onions and tomatoes declined substantially at the onset of the pandemic. Further, market distortions increased significantly for most commodities. Pulses experienced large price distortions between markets as well as mark-ups between retail and wholesale prices. We, however, do not see any major price distortions in the market for rice and wheat, which are controlled by Government's minimum support prices.
Keywords: 330; COVID-19; Food prices; Market distortion; Price dispersion; India